Advance care planning for patients with chronic respiratory diseases: a systematic review of preferences and practices. Issue 3 (6th November 2017) - Jabbarian, Lea J; Zwakman, Marieke; van der Heide, Agnes; Kars, Marijke C; Janssen, Daisy J A; van Delden, Johannes J; Rietjens, Judith A C; Korfage, Ida J
Abstract : Background: Advance care planning (ACP) supports patients in identifying and documenting their preferences and timely discussing them with their relatives and healthcare professionals (HCPs). Since the British Thoracic Society encourages ACP in chronic respiratory disease, the objective was to systematically review ACP practice in chronic respiratory disease, attitudes of patients and HCPs and barriers and facilitators related to engagement in ACP. Methods: We systematically searched 12 electronic databases for empirical studies on ACP in adults with chronic respiratory diseases. Identified studies underwent full review and data extraction. Results: Of 2509 studies, 21 were eligible: 10 were quantitative studies. Although a majority of patients was interested in engaging in ACP, ACP was rarely carried out. Many HCPs acknowledged the importance of ACP but were hesitant to initiate it. Barriers to engagement in ACP were the complex disease course of patients with chronic respiratory diseases, HCPs' concern of taking away patients' hopes and lack of continuity of care. The identification of trigger points and training of HCPs on how to communicate sensitive topics were identified as facilitators to engagement in ACP. Conclusions: In conclusion, ACP is surprisingly uncommon in chronic respiratory disease, possibly due to the complex disease course of chronic respiratory diseases and ambivalence of both patients and HCPs to engage in ACP. Providing patients with information about their disease can help meeting their needs. Additionally, support of HCPs through identification of trigger points, training and system-related changes can facilitate engagement in ACP. Systematic review registration number: CRD42016039787.